Simultaneous manipulation of scalable absorbance and the electronic bridge for efficient CO2 photoreduction. Issue 48 (30th November 2022) - Zhou, Xin; Zhang, Xin; Ding, Penghui; Zhong, Kang; Yang, Jinman; Yi, Jianjian; Hu, Qingsong; Zhou, Ganghua; Wang, Xiaozhi; Xu, Hui; Zhu, Xingwang
Abstract : An oxygen bridge structure was introduced into graphitic carbon nitride using a unique synthetic method. The presence of the oxygen bridge enables electron transfer and the reaction of CO2 molecules adsorbed on the surface to form CO. Abstract : Highly active, low-cost, and stable photocatalysts are the key point for the development of photocatalysis technology, which is one of the most promising advanced approaches to a greener future. As a nonmetallic polymer with high performance, graphitic carbon nitride (g-C3 N4 ) has a notable effect on photocatalytic CO2 reduction. However, the narrow light absorption limits its photocatalytic efficiency. In this work, we prepared red g-C3 N4 with the oxygen bridge structure (CSCN) using a grinding thermal polymerization method. The oxygen bridge structure provides more active sites, broadens the light absorption range, and improves the charge separation efficiency. Benefiting from the combined above advantages, CSCN exhibited a rate of photocatalytic reduction of CO2 to CO of 28.5 μmol g −1 h −1 . This work proposes a way to enhance the light absorption efficiency and CO2 reduction properties of g-C3 N4 .